Jasmonate-Induced Defense Mechanisms in the Belowground Antagonistic Interaction Between Pythium arrhenomanes and Meloidogyne graminicola in Rice - Verbeek, Ruben E. M.; Van Buyten, Evelien; Alam, Md Zahangir; De Vleesschauwer, David; Van Bockhaven, Jonas; Asano, Takayuki; Kikuchi, Shoshi; Haeck, Ashley; Demeestere, Kristof; Gheysen, Godelieve; Höfte, Monica; Kyndt, Tina (Frontiers in Plant Science, 2019)
Next to their essential roles in plant growth and development, phytohormones play a central role in plant immunity against pathogens. In this study we studied the previously reported antagonism between the plant-pathogenic oomycete Pythium arrhenomanes and the root-knot nematode Meloidogyne graminicola, two root pathogens that co-occur in aerobic rice fields. In this manuscript, we investigated if the antagonism is related to imbalances in plant hormone levels, which could be involved in activation of plant defense. Hormone measurements and gene expression analyses showed that the jasmonate (JA) pathway is induced early upon P. arrhenomanes infection. Exogenous application of methyl-jasmonate (MeJA) on the plant confirmed that JA is needed for basal defense against both P. arrhenomanes and M. graminicola in rice. Whereas M. graminicola suppresses root JA levels to increase host susceptibility, Pythium inoculation boosts JA in a manner that prohibits JA repression by the nematode in double-inoculated plants. Exogenous MeJA supply phenocopied the defense-inducing capacity of Pythium against the root-knot nematode, whereas the antagonism was weakened in JA-insensitive mutants. Transcriptome analysis confirmed upregulation of JA biosynthesis and signaling genes upon P. arrhenomanes infection, and additionally revealed induction of genes involved in biosynthesis of diterpenoid phytoalexins, consistent with strong activation of the gene encoding the JA-inducible transcriptional regulator DITERPENOID PHYTOALEXIN FACTOR. Altogether, the here-reported data indicate an important role for JA-induced defense mechanisms in this antagonistic interaction. Next to that, our results provide evidence for induced expression of genes encoding ERF83, and related PR proteins, as well as auxin depletion in P. arrhenomanes infected rice roots, which potentially further contribute to the reduced nematode susceptibility seen in double-infected plants.